Leveraging artificial intelligence for enhancing postgraduate teaching: a framework to engaging professional learners / Zoel-Fazlee Omar ... [et al.] - Omar, Zoel-Fazlee; Mior Harun, Mior Harris; Mohd Ishar, Nor Irvoni; Mustapha, Nur Arfah; Ismail, Zurina (UiTM Press, 2024)
In the contemporary landscape of postgraduate education, the strategic integration of Artificial Intelligence (AI) has gained prominence as a transformative approach for optimizing pedagogical experiences, particularly among professional learners. This paper presents a framework aimed at harnessing the potential of AI to elevate postgraduate teaching, focusing on fostering active engagement and meaningful learning interactions within the context of professional education. Following the PRISMA guidelines, this research conducts a systematic review of pertinent literature sourced from Scopus and other reputable databases. Studies encompassing empirical investigations, conceptual frameworks, and pedagogical models that explore the integration of AI in postgraduate education for professional learners are selected. A stringent search strategy and clear eligibility criteria ensure the inclusion of studies that contribute to the development of the proposed framework. Drawing from the findings of the systematic review, this paper proposes a multidimensional framework that strategically incorporates AI into postgraduate teaching for professional learners. This paper contributes a novel framework for integrating AI into postgraduate education, specifically tailored to the needs of professional learners. The synthesized framework serves as a pragmatic guide for educators, curriculum designers, and policymakers aiming to leverage AI’s potential to enrich professional education. By strategically combining AI technologies with pedagogical strategies, educators can empower professional learners to thrive in their careers, offering them a robust learning experience that resonates within their professional pursuits.